2005
DOI: 10.1007/s00234-005-1360-1
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging in 120 patients with intractable partial seizures: a preoperative assessment

Abstract: The aim of this study was to describe magnetic resonance imaging (MRI) findings in patients with medically intractable epilepsy and to compare different magnetic resonance (MR) sequences in order to establish a dedicated and shorter scan time imaging protocol of choice. One hundred and twenty patients with seizures that were refractory to medical treatment were assessed by MRI with spin-echo (SE) T1, fast spin-echo (FSE) T2, fluid-attenuated inversion recovery (FLAIR), inversion recovery (IR) and contrast-enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…For example, typical epileptogenic lesions diagnosed in patients with temporal lobe epilepsy are hippocampal atrophy/sclerosis, dysembryoplastic neuroepithelial tumors, gangliogliomas, postherpetic encephalitic gliosis, and posttraumatic encephalomalacia. 2,8,9 Until now, little was known about the epileptogenic lesions associated with IPICE. In our study, 13 patients (27%) with IPICE manifested tumors, 8 of whom had low-grade gliomas.…”
Section: Discussionmentioning
confidence: 99%
“…For example, typical epileptogenic lesions diagnosed in patients with temporal lobe epilepsy are hippocampal atrophy/sclerosis, dysembryoplastic neuroepithelial tumors, gangliogliomas, postherpetic encephalitic gliosis, and posttraumatic encephalomalacia. 2,8,9 Until now, little was known about the epileptogenic lesions associated with IPICE. In our study, 13 patients (27%) with IPICE manifested tumors, 8 of whom had low-grade gliomas.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that in this clinical scenario, MRI has a sensitivity of 84% with specificity of 70%, whereas the sensitivity of CT is approximately 62% [45]. MRI is particularly useful in the evaluation of mesial temporal sclerosis and cortical abnormalities that may be the cause of refractory seizures [46,47]. The data are limited on the additional value of specialized MRI sequences, such as diffusion tensor imaging, which may help to improve specificity in localization of the epileptogenic lesion in cases where conventional structural MRI is nonlesional [48].…”
Section: Variant 8: Children 1 Month To 18 Years Of Age Intractable Seizures or Refractory Epilepsymentioning
confidence: 99%
“…Epilepsy is a common neurological disease, affecting 0.5%-1% of the population, being refractory to medical therapy in 15%-30% of cases, in some of whom, neurosurgical treatment can be superior to long-term drug treatment, (Lefkopoulos A, Haritanti A, Papadopoulou E, Karanikolas D, Fotiadis N, Dimitriadis AS, 2005;Wiebe S, Blume WT, Girvin JP, Eliasziw M., 2001) especially in temporal lobe epilepsy (TLE) which is the most common form of focal epilepsy refractory to medical therapy in adults. (Engel J Jr., 2001) Patients with frontal lobe epilepsy (FLE), however, have a poorer outcome.…”
Section: Introductionmentioning
confidence: 99%